Nutritional properties of ogi powder and sensory perception of ogi porridge made from synthetic provitamin: a maize genotype - Akinsola, O.; Alamu, Emmanuel Oladeji; Otegbayo, B.; Menkir, A.; Maziya-Dixon, Busie (Frontiers Media, 2021)
Provitamin-A maize (PVA) with increased carotenoid content obtained through conventional breeding techniques has been largely successful in sub-Saharan Africa. This resulted in a need to evaluate their susceptibility, retention, and nutritional content during processing into local foods. This study evaluated the chemical, carotenoid composition, and retention of PVA, the phytic acid content in ogi powder, and the sensory perception of ogi porridge produced traditionally from the three novel PVA maize genotypes (PVA SYN HGAC0 Maize 1; PVA SYN HGBC0 Maize 2; and PVA SYN HGBC1 Maize 3) and one yellow maize variety (control). Chemical composition analyses showed significant differences (p < 0.05) in all parameters. The PVA ranged from 5.96 to 8.43 μg/g in Maize 2 and 3 before processing while the true percentage retention after processing into ogi powder ranged from 20.25 to 37.54% in Maize 1 and 2, respectively. In addition, there was a reduction in the phytate content of ogi powder, and Maize 2 contained the lowest (2.78 mg/g from 4.09 mg/g). Maize 2 genotype had the highest vitamin A contribution; it can meet 18.3% of the vitamin A requirements in children while in adult males and females (>19 years), 6.2 and 7.7%, respectively. Sensory evaluation showed that the ogi 3 porridge (Maize 3) was the most acceptable, followed by Maize 2. In conclusion, Maize 2 had the highest PVA, true retention of carotenoid, vitamin A contributions, and the second most acceptable ogi porridge with the lowest phytate content.